1994
DOI: 10.1159/000217873
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Value of Tissue Polypeptide Specific Antigen in Patients with Pancreatic Carcinoma

Abstract: We evaluated the clinical utility of a new tumor marker tissue polypeptide specific antigen (TPS) in the diagnosis of pancreatic carcinoma. Serum concentrations were determined in 113 patients with jaundice, in 18 patients with laboratory values suggesting cholestasis and in 60 patients with suspicion of chronic pancreatitis or pancreatic tumor. Twenty-four of these 191 patients had pancreatic carcinoma and 2 patients had carcinoma of the papilla of Vater. The highest median serum TPS value was detected in pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
11
2

Year Published

1996
1996
2013
2013

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 6 publications
2
11
2
Order By: Relevance
“…Our results are in agreement with other studies which reported that higher serum levels of CA19-9 were associated with the presence of distal metastases and worse prognosis of patients with pancreatic cancer [17,18]. In contrast, other authors have not found the relationship between CA19-9 value and the clinical advancement of pancreatic cancer [16,19]. …”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Our results are in agreement with other studies which reported that higher serum levels of CA19-9 were associated with the presence of distal metastases and worse prognosis of patients with pancreatic cancer [17,18]. In contrast, other authors have not found the relationship between CA19-9 value and the clinical advancement of pancreatic cancer [16,19]. …”
Section: Discussionsupporting
confidence: 92%
“…The last analyzed marker – TPS – in our and other studies was also significantly elevated in patients with PA [11,16]. It is known from the literature that TPS serum levels increased in other neoplastic diseases.…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…The tumour markers are rather crude measures of resectability and prognosis in patients with pancreatic cancer. Despite the fact the marker levels in our study were overall slightly lower than in previous studies of the same markers applied as diagnostic (17,19,21,22) and prognostic markers (4,10,14,23), none of the included patients were found to fit for pancreatic resection.…”
Section: Discussioncontrasting
confidence: 85%
“…In some studies CA 19-9 has been found to be superior to TPS (16)(17)(18), whereas in another study the contrary was shown (19). We found that the AUC was slightly higher for TPS than for CA19-9 and CEA, but the differences were not significant.…”
Section: Discussioncontrasting
confidence: 61%